Investigating elastic properties of soft biological tissues. - Brusseau, E. (IEEE Engineering in medicine and biology magazine)
We have developed a signal processing technique to map the axial strain distribution occurring in a medium exposed to a mechanical compression with RF ultrasound signals. This method is based on an adaptive and iterative estimation of local scaling factors, via the exploitation of phase information.